2021
DOI: 10.3390/bioengineering8070093
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Adipose Stem Cells Cell Sheets Transmittance

Abstract: In the field of cell therapy, the interest in cell sheet technology is increasing. To determine the cell sheet harvesting time requires experience and practice, and different factors could change the harvesting time (variability among donors and culture media, between cell culture dishes, initial cell seeding density). We have developed a device that can measure the transmittance of the multilayer cell sheets, using a light emitting diode and a light detector, to estimate the harvesting time. The transmittance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…The ASCs kept growing over time, forming a strong multilayer cell sheet ( Figure 1A ). The transmittance of these undifferentiated ASCCSs decreased at around 60% as reported in a previous publication but using different culture media ( Ochiai et al, 2021 ). Osteoblast cell sheets were engineered in 15 days.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The ASCs kept growing over time, forming a strong multilayer cell sheet ( Figure 1A ). The transmittance of these undifferentiated ASCCSs decreased at around 60% as reported in a previous publication but using different culture media ( Ochiai et al, 2021 ). Osteoblast cell sheets were engineered in 15 days.…”
Section: Resultssupporting
confidence: 80%
“…We understand that it is necessary to develop new tools and experiments to understand better the cell sheet physical properties as explained in this excellent review ( Efremov et al, 2021 ). Different physical properties could be studied, such as how the cell sheets can be stretched in one or two directions ( Homma et al, 2020 ; Huang et al, 2021 ), the nanoindentation ( Qian and Zhao, 2018 ), or optical properties ( Ochiai et al, 2021 ). Shimizu’s group reported that detached and stretched cardiomyocyte cell sheets from a temperature-responsive surface were longer, but that the cardiomyocyte cells had a unidirectional alignment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations